2011
DOI: 10.1063/1.3669526
|View full text |Cite
|
Sign up to set email alerts
|

Developments of scanning probe microscopy with stress/strain fields

Abstract: An innovative stress/strain fields scanning probe microscopy in ultra high vacuum (UHV) environments is developed for the first time. This system includes scanning tunneling microscope (STM) and noncontact atomic force microscope (NC-AFM). Two piezo-resistive AFM cantilever probes and STM probes used in this system can move freely in XYZ directions. The nonoptical frequency shift detection of the AFM probe makes the system compact enough to be set in the UHV chambers. The samples can be bent by an anvil driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…the diversification and deepening of research, some samples have shown novel characteristic changes under different test conditions (such as local stress on samples [3,4], multi-tip collaborative work [5][6][7], temperature change [8][9][10], magnetic field change [11][12][13][14], electrochemical regulation [15][16][17], etc), eliciting continuous interest. However, since the tunnel junction of STMs is often less than 1 nm [1], it tends to change drastically when adjusting the test environment of the sample, causing a collision of the sample and the tip, and then the test must be terminated.…”
Section: Introductionmentioning
confidence: 99%
“…the diversification and deepening of research, some samples have shown novel characteristic changes under different test conditions (such as local stress on samples [3,4], multi-tip collaborative work [5][6][7], temperature change [8][9][10], magnetic field change [11][12][13][14], electrochemical regulation [15][16][17], etc), eliciting continuous interest. However, since the tunnel junction of STMs is often less than 1 nm [1], it tends to change drastically when adjusting the test environment of the sample, causing a collision of the sample and the tip, and then the test must be terminated.…”
Section: Introductionmentioning
confidence: 99%
“…Capacitive sensors have been used in probes because of their high resolution [6][7][8]; however, capacitive sensors generally suffer from non-linearity, limited range and drift. The second type is the deformation sensing probe by strain gauges [2,[9][10][11][12]. The deformation of the membrane or cantilever caused by the tip ball's motion is detected by the strain gauges, usually made by semiconductor patterning techniques, based on the piezo-resistive effect.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement and characterization of various surface properties have been realized by using SPMs. Since the SPM measurement head is generally easy to dwarf, it is possible to be used in various environments such as ultrahigh vacuum, liquid, variable temperature, variable magnetic field, stress field, and so on [4]. By utilizing interaction between probe and surface, SPMs can be applied as versatile tools for nanotechnology such as atom operation, nano-deposition, nano-lithography, phase control and so on [5].…”
Section: Introductionmentioning
confidence: 99%